1942
DOI: 10.1104/pp.17.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saline Substrate on Hourly Levels of Carbohydrates and Inorganic Constituents of Barley Plants

Abstract: IntroductionSalinity considerations are likely to be an important feature of irrigation agriculture wherever it is practiced. The fact that a depressed growth of many plants results from even moderate accumulations of chloride and sulphate salts in soil solutions has a highly practical significance. From the standpoint of the investigator, it is particularly desirable that the mechanism of salt injury be as clearly understood as our present-day insight into biological processes will permit.The investigation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

1945
1945
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 13 publications
4
15
0
Order By: Relevance
“…The high concentrations of sugar phosphates in the source leaves of salt-stunted plants suggest that photosynthesis was not limiting for growth. These results are reminiscent of the earlier work of Gauch and Eaton (14) showing increased accumulation of sucrose and starch in the shoots of salt-stunted barley plants. This accumulation of metabolites in mature photosynthesizing leaves of saltstunted plants might be attributed to a reduced number of active sinks using these metabolites for growth.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The high concentrations of sugar phosphates in the source leaves of salt-stunted plants suggest that photosynthesis was not limiting for growth. These results are reminiscent of the earlier work of Gauch and Eaton (14) showing increased accumulation of sucrose and starch in the shoots of salt-stunted barley plants. This accumulation of metabolites in mature photosynthesizing leaves of saltstunted plants might be attributed to a reduced number of active sinks using these metabolites for growth.…”
Section: Discussionsupporting
confidence: 77%
“…The basis for the growth-suppressive effects of salinity is still moot. The results of these experiments and others (14,19,27) indicate a close link between disturbed transport of Pi and other metabolites, growth suppression, and leaf injury.…”
Section: Discussionmentioning
confidence: 83%
“…However, Cramer et al (1990) observed that the NAR of saltstressed plants was positively correlated with the relative growth rate but not with the LAR, and they suggested that these discrepancies were probably due to differences in the salinity treatments and plant species used. Gauch and Eaton (1942) suggested that salinity affects the utilization of photosynthates rather than photosynthesis itself in barley. Several studies showed that salinity increased the maintenance respiration (Rm) in plants (Schwarz and Gale 1981;Bloom and Epstein 1984;Rawson 1986).…”
Section: Discussionmentioning
confidence: 99%
“…7). Other studies on beaiis (63), sweet peas (37), and barley (20) grown oni sand cultures presented evidence that saline substrates induLce miarked accuimulatioin ofnonreducing sugars. In fact, these sugars were comparatively abunidant in plants of all treatments of the present study.…”
Section: (With Nine Figures)mentioning
confidence: 94%